Correlation of CLinical and Radiological with Postoperative Histopathological Diagnosis of Nasal Masses - Karki, Reeba; Pradhan, B; Thapa, N; Jha, A (Nepalese Journal of ENT Head and Neck Surgery, 2013)
Nepalese Journal of ENT Head and Neck Surgery, Vol. 3 Issue 1 (Jan-June 2012) Page 5-6 DOI: http://dx.doi.org/10.3126/njenthns.v3i1.8178